Effects of synthetic amendment on the growth of oil palm in sandy and top soil / Aqila Nor Ain - Nor Ain, Aqila (Faculty of Plantation and Agrotechnology, 2018)
This study is critical because it shows how synthetic amendments, which is Super Absorbent Polymers (SAPs) worked with different types of soil will affect the growth of oil palm seedlings. To get better plant growth performance, it requires enough water, fertilizer and light for photosynthesis. SAPs that act as soil moisture conditioner can help in solving sandy soils problems, improve water holding capacity and soil structure, ease the water absorption, avoid loss of nutrient in soil and water stress, reduce waste and give high porosity. Polyacrylamide, one of the SAPs type were used and this type was obtained from diapers. This experiment was carried out at a greenhouse where we can monitor the temperature and humidity changes. The oil palm seedling was grown under four different combination of medium. T1 (1 part of top soil: 1 part of SAP (1:1)) and T2 (1 part of sandy soil: 1 part of SAP (1:1)). As for control are, T3 (100% of sandy soil) and T4 (100% of topsoil). The arrangement is in a completely randomised design (CRD). Each treatment had 3 replications. Growth parameters are a stem height, plant biomass (aerial and root), leaf diameter, and leaf width. The results presented show oil palm seedlings managed to thrive on soil with SAPs. When comparing all treatments, top soil plus SAP give a substantial good impact on the growth of oil palm seedlings.